2009
DOI: 10.1103/physrevd.79.094022
|View full text |Cite
|
Sign up to set email alerts
|

SU(3)-breaking corrections to the hyperon vector couplingf1(0)in covariant baryon chiral perturbation theory

Abstract: We calculate the SU(3)-breaking corrections to the hyperon vector coupling f1(0) up to O(p 4 ) in covariant baryon chiral perturbation theory with dynamical octet and decuplet contributions. We find that the decuplet contributions are of similar or even larger size than the octet ones. Combining both, we predict positive SU(3)-breaking corrections to all the four independent f1(0)'s (assuming isospin symmetry), which are consistent, within uncertainties, with the latest results form large Nc fits, chiral quark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 23 publications
5
47
2
Order By: Relevance
“…Recently, it has been shown that a successful study of hyperon phenomenology can be achieved using the covariant approach of SU(3)-BχPT [18]. Examples include the description of the baryon-octet magnetic moments [19,20] the analysis of the semileptonic hyperon decays [18,21] and the prediction of the magnetic dipole moments and electromagnetic structure of the decuplet resonances [22]. The power counting is restored [11] using the so-called extended-onmass-shell (EOMS) renormalization scheme [23] and the contributions of decuplet resonances are systematically and explicitly considered [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that a successful study of hyperon phenomenology can be achieved using the covariant approach of SU(3)-BχPT [18]. Examples include the description of the baryon-octet magnetic moments [19,20] the analysis of the semileptonic hyperon decays [18,21] and the prediction of the magnetic dipole moments and electromagnetic structure of the decuplet resonances [22]. The power counting is restored [11] using the so-called extended-onmass-shell (EOMS) renormalization scheme [23] and the contributions of decuplet resonances are systematically and explicitly considered [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…The EOMS scheme has already been successfully applied to study many physical observables such as the magnetic moments [22,[29][30][31], the masses, and sigma terms [21,[32][33][34] of the octet and decuplet baryons, the hyperon vector couplings [35,36], the axial vector charges [37], the pionnucleon scattering [38,39], the nucleon Compton scattering [40], the neutral pion photo production [41], the scattering of pseudoscalar mesons off D=B mesons [42][43][44], the DD Ã scattering [45], and the Ξ cc masses and sigma terms [46,47]. It will be interesting to see how it describes the magnetic moments of the Ξ cc baryons, particularly from the perspective of lattice QCD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, we recall that the tendency of the SU(3) breaking correction observed here disagrees predictions of both the latest baryon ChPT result [11] and large N c analysis [8].…”
Section: Hyperon Vector Form Factors With 2+1 Flavor Dynamical Domainmentioning
confidence: 38%